Hadith #2313 - Sunan Abi Dawud - al-Bara' bin Azib bin al-Harith; Ishaq bin Rahwaya إسحاق بن راهويه; Isra'il bin Yonus bin Abi Ishaq إسرائيل بن يونس بن أبي إسحاق; Muhammad bin 'Abdullah bin al-Zubair محمد بن عبد الله أبو أحمد الزبيري; Nasr bin 'Ali bin Nasr bin 'Ali (Sunan Abi Dawud)
Ibn Abbas explained the following Qur’anic verse: “O ye who believe! fasting is prescribed for you as it was prescribed for those before you” During the lifetime of the Prophet (ﷺ), when the people offered night prayer, they were asked to abstain from food and drink and (intercourse with) women, they kept fast till the next night. A man betrayed himself and had intercourse with his wife after he had offered the night prayer, and he did not break his fast. So Allah, the Exalted, intended
Grade: Hasan Sahih

Hadith #4026 - Sunan Abi Dawud - Asma' bint Yazid bin al-Sakan; Badayl bin Maysarah بديل بن ميسرة; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Ishaq bin Rahwaya إسحاق بن راهويه; Mua'dh bin Hisham bin Aby معاذ بن هشام بن أبي عبد الله; Shar bin Hushab al-Asha'ri شهر بن حوشب الأشعري (Sunan Abi Dawud)
No clothing was dearer to be Messenger of Allah (ﷺ) than shirt.
Grade: Sahih